Predictors and prevalence of anemia, among children aged 6 to 59 months in shebelle zone, somali region, eastern Ethiopia: A cross sectional study - Abdi Guled, Rashid; Mamat, Nik Mazlan; Balachew, Tefera; Mohd Abu Bakar, Wan Azdie; Assefa, Nega (International Journal of Development Research (IJDR), 2017)
Introduction: Anemia is one of the major public health problems in the world. Anemia affected 273.2 million under five children in 2011 of which 62.2 % occur to Sub-Saharan Africa. Ethiopia is one of the seriously affected countries in this region. Hence, the aim of the study is to assess the prevalence, and the predictors of preschool children anemia in Shebelle Zone of Somali Region. Methods: A cross sectional study was conducted on 397 children 6 – 59 months and their mothers/caregivers in Gode and Adadle districts. A face-to-face interview for mothers/caregivers was done using a structured questionnaire, blood hemoglobin level of the children were measured using HemoCue 301. Anemia in this age group was diagnosed if hemoglobin level was less than 11g/dl. Bivariate and multivariable analysis was used to isolate independent predictors for under-five anemia. Results: The mean hemoglobin level of preschool children was 9.66 ± 1.75 g/dl, while the anemia prevalence was 72%, out of which 20%, 46%, and 6% were mild, moderate, and severe anemia, respectively. Children ≤ 24 months were nearly twice (AOR = 1.888, 95% CI = 1.092, 3.362) more likely to develop anemia, Male children were more affected by anemia (AOR = 1.66, 95% CI = 1.001, 2.742). Unprotected drinking water were nearly five times (AOR = 4.88, 95% CI = 2.204, 10.820) more likely to develop anemia, and children having sing of diseases for the last two weeks were more than three times (AOR=3.44, 95% CI = 1.869, 6,321) more likely to be anemic. Conclusion and recommendation: The mean hemoglobin level of this studied population was below the cut off for anemia (11g/dl), and the anemia prevalence in this study is very high, and approximately fifty percent of them are moderately anemic. Behavior change communication with early starting breastfeeding, de-worming, drinking clean, and boiled water, proper using of insecticide treated nets, environmental managements and other services are highly required.